Respuesta :
Answer: y3−1y3=234
Step-by-step explanation:
y−1y=6
(y−1y)3=63
y3−3y+3y−1y3=216
y3−1y3=216+3(y−1y)=216+3(6)
not sure:)
Answer:
So we start with
y - (1/y) = x
if we cube both sides we get
y^3 - 3y^2*(1/y) + 3y*1/(y^2) - 1/(y^3) = x^3
which is the same as
y^3 - 1/(y^3) = x^3 + 3y^2*(1/y) - 3y*1/(y^2)
which is equal to
y^3 - 1/(y^3) = x^3 + 3y - 3*(1/y)
and since x = y - (1/y), that means 3x = 3y - 3*(1/y). So we can substitute 3x into the equation and we get:
y^3 - 1/(y^3) = x^3 + 3x
And that's your answer.